The Role of Forensic Accounting in Combating Financial Fraud in the Digital Age - Setyo Prihanto; Ahmad Hasan Muzaky; Bima Widhi Yuliantoro (International Forum of Researchers and Lecturers, 2024)
Financial fraud has become a persistent issue with the rise of online transactions and digital platforms. This paper explores the evolving role of forensic accountants in identifying and preventing fraud in the digital age. Through case studies and recent examples of financial crimes, the study evaluates the effectiveness of forensic accounting techniques such as data analytics, digital forensics, and cyber risk assessment. The paper also discusses the regulatory landscape and suggests strategies for improving fraud detection through technological innovation in accounting.